Flow carbonylation of sterically hindered ortho-substituted iodoarenes - Mallia, Carl J.; Walter, Gary C.; Baxendale, Ian R. (Beilstein Journal of Organic Chemistry, 2016)
The flow synthesis of ortho-substituted carboxylic acids, using carbon monoxide gas, has been studied for a number of substrates. The optimised conditions make use of a simple catalyst system compromising of triphenylphosphine as the ligand and palladium acetate as the pre-catalyst. Carbon monoxide was introduced via a reverse “tube-in-tube” flow reactor at elevated pressures to give yields of carboxylated products that are much higher than those obtained under normal batch conditions.
Keywords: carbon monoxide; carbonylation of ortho-substituted substrates; flow chemistry; gases in flow; “tube-in-tube”

(untitled) - Miller, P. W.; Long, N. J.; de Mello, A. J.; Vilar, R.; Passchier, J.; Gee, A. (Chem. Commun., 2006)

(untitled) - Rahman, M. T.; Fukuyama, T.; Kamata, N.; Sato, M.; Ryu, I. (Chem. Commun., 2006)

(untitled) - Miller, P. W.; Long, N. J.; de Mello, A. J.; Vilar, R.; Audrain, H.; Bender, D.; Passchier, J.; Gee, A. (Angew. Chem., Int. Ed., 2007)

(untitled) - Miller, P. W.; Jennings, L. E.; deMello, A. J.; Gee, A. D.; Long, N. J.; Vilar, R. (Adv. Synth. Catal., 2009)

(untitled) - Gong, X.; Miller, P. W.; Gee, A. D.; Long, N. J.; de Mello, A. J.; Vilar, R. (Chem. – Eur. J., 2012)

(untitled) - Koos, P.; Gross, U.; Polyzos, A.; O'Brien, M.; Baxendale, I.; Ley, S. V. (Org. Biomol. Chem., 2011)

(untitled) - Mercadante, M. A.; Leadbeater, N. E. (Org. Biomol. Chem., 2011)

(untitled) - Brancour, C.; Fukuyama, T.; Mukai, Y.; Skrydstrup, T.; Ryu, I. (Org. Lett., 2013)

(untitled) - Fukuyama, T.; Mukai, Y.; Ryu, I. (Beilstein J. Org. Chem., 2011)

(untitled) - Gross, U.; Koos, P.; O'Brien, M.; Polyzos, A.; Ley, S. V. (Eur. J. Org. Chem., 2014)

(untitled) - Brennführer, A.; Neumann, H.; Beller, M. (Angew. Chem., Int. Ed., 2009)

(untitled) - Wu, X.-F.; Neumann, H.; Beller, M. (Chem. Rev., 2013)

(untitled) - Brennführer, A.; Neumann, H.; Beller, M. (ChemCatChem, 2009)

(untitled) - Grigg, R.; Mutton, S. P. (Tetrahedron, 2010)

(untitled) - Barnard, C. F. J. (Org. Process Res. Dev., 2008)

(untitled) - Daniewski, A. R.; Liu, W.; Püntener, K.; Scalone, M. (Org. Process Res. Dev., 2002)

(untitled) - Ashfield, L.; Barnard, C. F. J. (Org. Process Res. Dev., 2007)

(untitled) - Cross, R. J.; Kennedy, A. R.; Muir, K. W. (Acta Crystallogr., Sect. C: Cryst. Struct. Commun., 1995)

(untitled) - Baumann, M.; Baxendale, I. R. (Beilstein J. Org. Chem., 2015)

(untitled) - Pinho, V. D.; Gutmann, B.; Miranda, L. S. M.; de Souza, R. O. M. A.; Kappe, C. O. (J. Org. Chem., 2014)

(untitled) - Baxendale, I. R.; Brocken, L.; Mallia, C. J. (Green Process. Synth., 2013)

(untitled) - McQuade, D. T.; Seeberger, P. H. (J. Org. Chem., 2013)

(untitled) - Baxendale, I. R. (J. Chem. Technol. Biotechnol., 2013)

(untitled) - Pastre, J. C.; Browne, D. L.; O'Brien, M.; Ley, S. V. (Org. Process Res. Dev., 2013)

(untitled) - Wiles, C.; Watts, P. (Green Chem., 2012)

(untitled) - Anderson, N. G. (Org. Process Res. Dev., 2012)

(untitled) - Wegner, J.; Ceylan, S.; Kirschning, A. (Adv. Synth. Catal., 2012)

(untitled) - Malet-Sanz, L.; Susanne, F. (J. Med. Chem., 2012)

(untitled) - Wegner, J.; Ceylan, S.; Kirschning, A. (Chem. Commun., 2011)

(untitled) - Yue, J.; Chen, G.; Yuan, Q.; Luo, L.; Gonthier, Y. (Chem. Eng. Sci., 2007)

(untitled) - Brzozowski, M.; O'Brien, M.; Ley, S. V.; Polyzos, A. (Acc. Chem. Res., 2015)

(untitled) - O'Brien, M.; Baxendale, I. R.; Ley, S. V. (Org. Lett., 2010)

(untitled) - Yang, L.; Jensen, K. F. (Org. Process Res. Dev., 2013)

(untitled) - Fukuyama, T.; Totoki, T.; Ryu, I. (Green Chem., 2014)

(untitled) - Immirzi, A.; Musco, A. (Inorg. Chim. Acta, 1977)

(untitled) - Clavier, H.; Nolan, S. P. (Chem. Commun., 2010)

(untitled) - van Leeuwen, P. W. N. M.; Kamer, P. C. J.; Reek, J. N. H.; Dierkes, P. (Chem. Rev., 2000)

(untitled) - Kamer, P. C. J.; van Leeuwen, P. W. N. M.; Reek, J. N. H. (Acc. Chem. Res., 2001)

(untitled) - van der Veen, L. A.; Keeven, P. H.; Schoemaker, G. C.; Reek, J. N. H.; Kamer, P. C. J.; van Leeuwen, P. W. N. M.; Lutz, M.; Spek, A. L. (Organometallics, 2000)

(untitled) - Kaupmees, K.; Trummal, A.; Leito, I. (Croat. Chem. Acta, 2014)

Stereochemistry of organic compounds - Eliel, E. L.; Wilen, S. H.; Mander, L. N. (Wiley & Sons, 1994)

(untitled) - Baumann, M.; Baxendale, I. R.; Kuratli, C.; Ley, S. V.; Martin, R. E.; Schneider, J. (ACS Comb. Sci., 2011)